2021
DOI: 10.1002/ett.4200
|View full text |Cite
|
Sign up to set email alerts
|

Replication‐aware secure resource administration scheme for Internet of Things‐smart city applications

Abstract: The distributed and heterogeneous nature of the Internet of Things (IoT) paradigm provides backhauled support for different smart-city applications. As it provides ubiquitous access to resources and replicated services, the threat for security remains firm for different applications. The concept of cybersecurity in the IoT-smart-city combination grants promising outcomes in securing the physical and service-centric resources from external threats. This article proposes to improve the protection of the IoT serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Bhargava et al [ 114 ] suggested enhancing the experience in smart cities by addressing security and privacy issues in IoT platforms and provided an overview of how ML and DL could be implemented in IoT devices and services. Al Solami [ 115 ] presented a framework for secure resource administration that enhances IoT services in smart city applications by preventing replication. This involves the distribution of the cloud, networks, IoT platforms, and sensors.…”
Section: Cybersecurity In Smart Citiesmentioning
confidence: 99%
“…Bhargava et al [ 114 ] suggested enhancing the experience in smart cities by addressing security and privacy issues in IoT platforms and provided an overview of how ML and DL could be implemented in IoT devices and services. Al Solami [ 115 ] presented a framework for secure resource administration that enhances IoT services in smart city applications by preventing replication. This involves the distribution of the cloud, networks, IoT platforms, and sensors.…”
Section: Cybersecurity In Smart Citiesmentioning
confidence: 99%